Clinical profile of cutaneous adverse effects of epidermal growth factor receptor inhibitors: A prospective observational study of 76 cases - Neerja Saraswat; Aradhana Sood; Dharmesh Kumar; Rajesh Verma; Kumar Sushil (Wolters Kluwer Medknow Publications, 2019)
Background: Epidermal growth factor receptor (EGFR) inhibitors are an extensively utilized class of chemotherapeutic agents which form an integral component of treatment in solid organ malignancies such as non-small-cell lung carcinoma, pancreatic carcinoma, colorectal carcinoma, and head and neck carcinoma. It has two subclasses: epidermal growth factor inhibitors (erlotinib) and monoclonal antibody (cetuximab). A wide array of cutaneous adverse effects has been attributed to this class of drugs, such as papulopustular eruptions, paronychia, xerosis, and changes in hair and nails. Materials and Methods: A total of 76 cases of various malignancies on EGFR inhibitors who developed cutaneous side effects while on therapy and reported or referred to us by oncologists from January 2017 to January 2018 were included in the study. All the patients who were on other associated medications or radiotherapy were excluded. Result: In all, 45 (59.2%) were males and 31 (40.7%) were females. Non-small-cell lung carcinoma was the most common carcinoma in 32 (42.1%) patients, and cetuximab was the most common drug in 29 (38.1%) cases. Papulopustular eruptions were seen in 61 (80.2%) patients, xerosis in 31 (40.7%), mucositis in 6 (7.8%), hair growth problems in 4 (5.6%), and paronychia and pyogenic granuloma in 2 (2.6%) patients each. Conclusion: Although most of the skin toxicities associated with EGFR inhibitors can be managed conservatively, a critical analysis of the cases that are significantly affected due to these side effects is required in cohesion with the treating oncologist to improve the therapeutic compliance of the drug.